2008
DOI: 10.1152/ajpheart.00748.2008
|View full text |Cite
|
Sign up to set email alerts
|

Deficient BH4production via de novo and salvage pathways regulates NO responses to cytokines in adult cardiac myocytes

Abstract: Adult rat cardiac myocytes typically display a phenotypic response to cytokines manifested by low or no increases in nitric oxide (NO) production via inducible NO synthase (iNOS) that distinguishes them from other cell types. To better characterize this response, we examined the expression of tetrahydrobiopterin (BH4)-synthesizing and arginine-utilizing genes in cytokine-stimulated adult cardiac myocytes. Intracellular BH4 and 7,8-dihydrobiopterin (BH2) and NO production were quantified. Cytokines induced GTP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…Indeed, DHFR protein levels are significantly decreased in streptozotocin-induced diabetic mice, and diabetes-induced impairment of myocyte function is exacerbated after treatment of the mice with MTX (25). Furthermore, because of the lack of DHFR activity, adult cardiac myocytes have limited capacity to synthesize BH4 after cytokine stimulation following treatment of rat cardiac allograft recipients with sepiapterin (26). An insufficiency of DHFR may also explain results obtained in hypercholesterolemic rabbits where prolonged exposure to sepiapterin impaired vasorelaxation despite repletion of endogenous BH4 (27).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, DHFR protein levels are significantly decreased in streptozotocin-induced diabetic mice, and diabetes-induced impairment of myocyte function is exacerbated after treatment of the mice with MTX (25). Furthermore, because of the lack of DHFR activity, adult cardiac myocytes have limited capacity to synthesize BH4 after cytokine stimulation following treatment of rat cardiac allograft recipients with sepiapterin (26). An insufficiency of DHFR may also explain results obtained in hypercholesterolemic rabbits where prolonged exposure to sepiapterin impaired vasorelaxation despite repletion of endogenous BH4 (27).…”
Section: Discussionmentioning
confidence: 99%
“…It is no wonder that the GFRP mRNA level is downregulated by the cytokine trio; thus, decreasing the GTPCH/GFRP complex and enhancing BH4 synthesis (48,49). However, GFRP mRNA expression is upregulated in smooth muscle cells of rat aorta (50) and adult rat cardiac myocytes (51). Moreover, GTPCH activity is not affected by changes in GFRP expression, suggesting that endothelial GTPCH expression is the primary determinant of BH4 levels (52).…”
Section: Transcriptional Regulation Of Gtpchmentioning
confidence: 99%
“…Although both eNOS and nNOS exist in the heart (89), the selective nNOS inhibitor inhibits cardiac superoxide production more than an iNOS inhibitor (14). However, DHFR mRNA and protein are not detected in adult rat cardiac myocytes (51). According to MPP + -induced toxicity studies in rat cerebellar granule neurons (15) and neuroblastoma cells transfected with human nNOS (87), MPP + increases superoxide generation, probably through impaired mitochondria, and diminishes the BH4/BH2 ratio.…”
Section: Interplay Between Bh4 and Nosmentioning
confidence: 99%
“…Both studies concluded that the beneficial effects of BH 4 or sepiapterin were NO or NOS independent, suggesting alternative mechanisms of action. Indeed, we concluded that the antirejection effect of sepiapterin was rather mediated, at least in part, by an action on immune cell proliferation based upon decreased IL-2 expression.Previously, we found that adult cardiac myocytes despite expression of GTPCH mRNA and protein have a defective basal and cytokine-stimulated synthesis of BH 4 via the de novo synthesis pathway and impaired synthesis via the salvage pathway in contrast with that typically seen in neonatal cardiac myocytes (7,26). In this context, we surmised that the beneficial effects of exogenous pterin administration on acute cardiac rejection was unlikely mediated via a mechanism of action to significantly change the intracellular BH 4 levels within cardiac myocytes per se.…”
mentioning
confidence: 92%
“…Previously, we found that adult cardiac myocytes despite expression of GTPCH mRNA and protein have a defective basal and cytokine-stimulated synthesis of BH 4 via the de novo synthesis pathway and impaired synthesis via the salvage pathway in contrast with that typically seen in neonatal cardiac myocytes (7,26). In this context, we surmised that the beneficial effects of exogenous pterin administration on acute cardiac rejection was unlikely mediated via a mechanism of action to significantly change the intracellular BH 4 levels within cardiac myocytes per se.…”
mentioning
confidence: 92%